Answer:
1) x = 4; y = -2
Step-by-step explanation:
1)
2x - y = 10;
x + y = 2
In order to do the elimination process, you must find two variables (either the x values or the y values) that are the exact opposites of each other. In this case, it isn't too hard since we have 1y and -1y, so now we eliminate them.
2x = 10;
x = 2
Now we add up both sides, so that it turns into 1 equation.
3x = 12;
Now we solve for one x
x = 4;
Now, we use this value and input it in both of the original equations to find and check for the other value, y.
2(4) - y = 10
8 - y = 10
-y/-1 = 2/-1
y = -2;
(4) + (-2) = 2
Does that help?